Barriers and facilitators to engagement with between-session work for low-intensity Cognitive Behavioural Therapy (CBT)-based interventions: a qualitative exploration of practitioner perceptions - Mia Bennion; Amy Blakemore; Karina Lovell; Penny Bee (BMC Psychiatry)
Abstract Background To address the growing demand for psychological treatment, healthcare providers are increasingly utilising low-intensity interventions, characterised by reduced practitioner contact and emphasis on independent patient engagement with therapeutic materials through between-session work (BSW). While BSW is critical for maximising treatment outcomes, patients and practitioners report challenges with its completion. Research identifying factors influencing between-session engagement in Cognitive Behavioural Therapy (CBT) has largely focused on high-intensity CBT, limiting understanding within low-intensity contexts. Methods This study explored practitioner perspectives on the barriers and facilitators of BSW engagement within low-intensity CBT-based interventions. Using interpretive description methodology, 22 Psychological Well-being Practitioners (PWPs) from UK National Health Service (NHS) Talking Therapies services were interviewed. Inductive and deductive framework analysis was used to crossmatch data to an existing conceptual model of predictors for CBT BSW engagement. Results Practitioners identified patient-level barriers including passive treatment expectations, comorbid health conditions, social stressors, and reduced mental health literacy, particularly among ethnic minority populations. Practitioner-level facilitators involved clear task planning and personalised BSW tailored to patients’ sociocultural environments. Organisational recommendations emphasised the need for diverse workforces and adequate training in culturally sensitive care. Conclusions Findings underscore the importance of practitioner behaviours in optimising patient engagement between-sessions, offering clear directions to enhance treatment outcomes in globally adopted low-intensity interventions.